NUMERICAL RESULTS OF MIXED CONVECTION FLOW OVER A FLAT PLATE WITH THE IMPOSED HEAT AND ANGLE OF INCLINATION - Mohammad Ghani (Universitas Negeri Gorontalo, 2021)
In this paper, the numerical results of mixed convection flow over a flat plate with the imposed heat and different angles of inclination are established by applying the finite difference method of Crank-Nicolson. We further compare these numerical results with the case of non-mixed convection flow. The velocity and temperature profiles are decreased when the different values of the Prandtl number (Pr) are increased. Meanwhile, the velocity profiles are increased, when the different values of angle of inclination (alfa) and mixed convection parameter (lambda) are increased. The mixed convection flow case (lambda=1.5) is affected by the external force, so the velocity of convection flow is higher than the non-mixed case (lambda=0).